Pancreatico-enteric fistula post pancreatic duct ligation for delayed haemorrhage complicating pancreaticoduodenectomy. (2016) - Vijay, Adarsh; Noaman, Islam; Mahfouz, Ahmed; Khawar, Mahwish; Khalaf, Hatem; Elaffandi, Ahmed
Highlights: Delayed post-pancreatectomy haemorrhage in association with pancreatic fistula is a grave complication. Pancreatic duct occlusion may be considered in hemodynamically unstable patients. Spontaneous development of a pancreatico-enteric fistula despite ligation of the pancreatic duct has never been reported to date. Abstract: Introduction: Pancreatic fistula remains the main cause for postoperative morbidity following pancreaticoduodenectomy. The coincidence of sentinel bleed prior to post pancreatectomy haemorrhage (PPH) and pancreatic fistula is associated with very high mortality. Presentation of case: We report a case of pancreaticoduodenectomy complicated by postoperative leak and hematemesis. Severe delayed haemorrhage from the pancreatico-jejunostomy necessitated re-laparotomy and complete disconnection of the pancreatic anastomosis. Hemodynamic instability precluded a pancreatectomy or creation of a new anastomosis. A follow up MRI done 3 weeks after the patient's discharge demonstrated a fistulous tract causing a communication between both the pancreatic and biliary systems and the enteric loop. Discussion: Spontaneous development a pancreatico-enteric fistula despite ligation of the pancreatic duct and complete disconnection of the pancreatic anastomosis has never been reported in literature to date. Conclusion: Pancreatic duct occlusion may be considered over a completion pancreatectomy or revisional pancreatic anastomosis in hemodynamically unstable and challenging cases.